ADA APA DENGAN MEME #AADC2: Sepotong Cerita tentang Budaya Partisipatif - Elvina, Elvina (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2016)
The phenomenon of memes has penetrated social media a few years ago, not least on Instagram. Even phenomenal movie sequels like AADC2 are inseparable from this phenomenon. The emergence of # AADC2 memes on Instagram from the perspective of media and cultural studies reflects interesting social meanings to explore. This study is qualitative research to see social meaning in # AADC2 memes on Instagram. The author collects data online through internet searches and interviews with creators and social media observers as a primary data amplifier. To find the social meaning behind the # AADC2 meme phenomenon on Instagram, the authors use Theo van Leeuwen's social semiotic analysis knife which includes four key elements, namely discourse, genre, style, and modality. The results of the analysis are then linked to the concept of representation through Foucault's perspective which emphasizes the focus on discourse, knowledge, and power as well as questions related to the subject. In this study, the authors found that meme # AADC2 is a product of participatory culture. Then the authors describe each of the social meanings contained in a meme as a representation of participatory culture through the constructionist viewpoint of Michael Foucault.